Frequency of reported cases of developmental dysplasia of the hip in Kurdistan region/Iraq - Doski, Jagar Omar; Mazin Alabbasi, Ahmed (Zanco Journal of Medical Sciences (ZJMS), 2025)
Background and objectives: Developmental dysplasia of the hip (DDH) incidence and prevalence varies with ethnicity and geographic location. In Iraq, especially in the Kurdistan Region, this information is not yet clear. This study aimed to find the total number of reported DDH cases and to estimate the incidence and prevalence. Methods: This cross-sectional study collected data from three governmental places of national sources of database (child disabilities centers, General Directory of Health, and General Directory of Statistics) in the three governments of Kurdistan Region/Iraq (Erbil, Sulaymania, and Duhok). The data included: the number of reported cases of DDH, live births, and population for each year and each government separately. The incidence was calculated by dividing the number of DDH cases per 1000 live births for each year, and prevalence by dividing all the cases of DDH per 1000 of population for each year. Then the average (mean) incidence and prevalence of each government was calculated. Finally, the average (mean) incidence and prevalence for the whole region (the three governments together) were calculated. Results: The required data from the determined sources were available for the last 25 years (1998-2022). The total number of reported cases of DDH during this period was 44972 cases. The average incidence of DDH cases in Kurdistan Region/Iraq was 18.2 cases per 1000 live births per year, the highest -22.9- in the Duhok government and the lowest -13.8- in the Erbil government. The average prevalence of DDH cases among the population in the region was 4.65 per 1000 in the last 25 years (the highest -8.93- in the Duhok government, and the lowest -2.35- in the Sulaymania government). Conclusion: The incidence of DDH cases in the Kurdistan region in the last 25 years was 18.2 cases per 1000 live births per year and the prevalence was 4.65 cases per 1000 of the population. The highest incidence and prevalence were reported in the Duhok government.